Bis-iridoids and other constituents from Scabiosa semipapposa. (June 2022) - Bendamene, Samia; Boutaghane, Naima; Sayagh, Charlotte; Alabdul Magid, Abdulmagid; Kabouche, Zahia; Bensouici, Chawki; Voutquenne-Nazabadioko, Laurence
Abstract: Six undescribed bis-iridoids named Semipapposiridoids A–F (1–6) together with seventeen known compounds were obtained from the roots and aerial parts of Scabiosa semipapposa Salzm. ex DC. Among the known compounds, three lignans were isolated for the first time in Scabiosa species, whereas the other known constituents including iridoids, phenol glycosides and flavonoids were previously isolated from Scabiosa sp . Their structures were assigned on the basis of extensive 1D- and 2D NMR experiments ( 1 H, 13 C, COSY, TOCSY, NOESY, HSQC, HMBC), mass spectrometry HR-ESI-MS and by comparison of their spectral data with those of literature values. To the best of our knowledge, this should be the first report on the bis-iridoids content of this plant; furthermore, the fact that the plant is rich in mono-and bis-iridoids will support chemotaxonomy of the genus. The total phenolic and flavonoid contents of the 80% MeOH extracts and fractions were evaluated, with their antioxidant activities using three different methods, namely DPPH, ABTS and CUPRAC. Most of the fractions showed a moderate to good antioxidant activity compared to the standards BHA and BHT. Graphical Abstract: ga1 Highlights: Six undescribed bis-iridoids were isolated from aerial parts of Scabiosa semippaposa Salzm. ex DC. Three known lignans are described for the first time in Scabiosa. The structures of isolated compounds were elucidated by NMR and HR-ESI-MS analyses Total phenolic contents and antioxidant activities were evaluated